Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.4103/0189-6725.170196
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal atresia: Diagnosis and prognosis in Dakar, Senegal

Abstract: Background:Oesophageal atresia is a neonatal emergency surgery whose prognosis has improved significantly in industrialised countries in recent decades. In sub-Saharan Africa, this malformation is still responsible for a high morbidity and mortality. The objective of this study was to analyse the diagnostic difficulties and its impact on the prognosis of this malformation in our work environment.Patients and Methods:We conducted a retrospective study over 4 years on 49 patients diagnosed with esophageal atresi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 27 publications
(33 reference statements)
4
14
0
Order By: Relevance
“…This finding was consistent with other reports. [ 13 , 30 ] Another independent risk factor for mortality in the present study was respiratory failure, which was consistent with other findings. [ 4 , 26 ] Respiratory failure caused by gastric fluid reflux into the lungs could increase the risk of mortality.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This finding was consistent with other reports. [ 13 , 30 ] Another independent risk factor for mortality in the present study was respiratory failure, which was consistent with other findings. [ 4 , 26 ] Respiratory failure caused by gastric fluid reflux into the lungs could increase the risk of mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have indicated that CHD is the most common congenital malformation associated with EA, [ 3 , 15 , 25 ] and major CHD is considered an important risk factor for mortality in EA. [ 2 , 8 , 13 ] However, in a large sample survey conducted by Rokitansky et al, [ 25 ] the most common malformations in neonates with EA were cardiac defects (23.3%, 72/309), and a majority of the defects were simple CHD (83.3%, 60/72). In a nationwide survey conducted in the United States, most cardiovascular malformations were also simple CHD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Major cardiac anomalies, severe prematurity and pre-operative estimation of long distance with bronchoesophagoscopy have been proposed as criteria to proceed to staged correction to avoid stenosis. [ 11 12 13 ] There is no precise definition of long-gap oesophageal atresia. Researchers proposed to consider as such, any atresia that cannot be repaired with a single operation.…”
Section: Discussionmentioning
confidence: 99%